Improving Interprofessional Understanding via Interprofessional Case Conferences - Daniel Erb; Victoria Kaprielian; Patricia Dieter; Brenda Nevidjon; Barbara Eldredge; Randa McNamara (Association of American Medical Colleges, 2011)
Abstract Introduction Using a case study format with standardized patients, Doctor of Physical Therapy (DPT), Medical Doctor (MD), nursing (N), Doctor of Pharmacy (Pharm D) and physician assistant (PA) learners work as collaborative, interprofessional teams to solve a "medical mystery" regarding their standardized patient. Methods Under the direction of interprofessional pairs of DPT, MD, N, Pharm D and PA facilitators, learners receive minimal information about their "patient" and then must rely on each other to develop and execute an interview strategy to obtain appropriate information from their standardized patient to find out why that patient has come to see them. Learners also develop an evaluation strategy and assess the patient's subjective and objective findings in order to develop a plan of care. Students then work as a team to counsel the standardized patient on the best manner to treat their specific complaints. Facilitators guide the learners through this process. Once all groups complete their counseling sessions, all participants meet for a wrap up session to discuss what the patient had and the key points of interprofessional care to best treat the patients concerns and diagnoses. Results Learner evaluations and feedback indicate a high degree of satisfaction with the Interprofessional Case Conference (ICC). Some selected comments received from evaluation forms are: "We need more of these...", "I had no idea what other providers did...", and "I learned so much. I'll be back." Mean overall evaluations of the experience are 4.7 on a 5-point Likert scale. Through the ICC learners experience what it is like to be a team in providing care to a patient. They also gain an appreciation, in a safe environment, of the role of other health care providers in providing best-practice care. Discussion The current trajectory of systems for delivery of health care in America is unsustainable. In the future, health care must be more patient-focused, community-based, and delivered by collaborative, interprofessional teams of providers. To prepare the next generation of providers for new models of care delivery, it is essential that providers learn to work effectively in an interprofessional team. The ICC provides an experience for learners from different health disciplines to better understand the roles of other disciplines in the care of a standardized patient.